Cognitive Function Differences on Elderlies (> 50 years) Examined from Daily Physical Activity Intensity Differences - Kukuh Pambuka Putra; Sanfia Tesabela Messakh; Yosta Doni Adhitya (Universitas Pendidikan Indonesia, 2019)
The general retirement age is 50-60 year old related to the assumption that, as people get older, a person will experience degeneration of brain cells which results in cognitive function decrease that affects work quality and productivity. Physical activity is believed to help reduce the cognitive function decrease in elderlies and provide opportunities to extend the productive period. This study was aimed at finding out the cognitive function differences in physically active elderlies and physically inactive elderlies, as well as the relationship between the level of daily physical activity and cognitive function of the elderlies. This study was an observative analytic study involving 90 elderlies ( 50 years) grouped into 2 groups based on the intensity of their daily physical activities. The instrument used for measuring physical activity level was GPAQ and the cognitive function measurement instrument was MMSE. The data obtained were analyzed by independent t-test and correlation test. The results showed a significant cognitive function difference (p 0.05) in the high physical activity group (KT) and the low physical activity group (KR). Correlation test showed a strong relationship (p 0.05) between the intensity of daily physical activity and cognitive function of the elderlies.